Role of Negative Pressure Wound Care and Hyperbaric Oxygen Therapy for Sternal Wound Infections After Pediatric Cardiac Surgery. Issue 4 (July 2018) - Copeland, Hannah; Newcombe, Jennifer; Yamin, Feras; Bhajri, Khaled; Mille, Vanessa Ayer; Hasaniya, Nahidh; Bailey, Leonard; Razzouk, Anees J.
Background: Sternal wound infections after pediatric cardiac surgery are uncommon but can be morbid. Methods: We describe an institutional protocol for complicated sternal wounds utilizing hyperbaric oxygen therapy (HBO) and negative pressure wound therapy (NPWT). Participants: A retrospective chart review (2001-2013) of 4, 028 pediatric cardiac operations in 3, 264 patients less than 18 years of age. Results: Fifty-three patients (1.62%; 53/3, 264) were diagnosed with clinical sternal wound infections. There were 27 (50.9%) males and 26 (49.1%) females. Thirty-seven (69.8%) patients received antibiotics and/or debridement; sixteen (30.2%) patients had more complicated infections requiring NPWT and/or HBO therapy. The time to heal for wounds treated with HBO and HBO + NPWT was a mean of 43.75 (±24.27) days (range: 21-98 days; median: 35 days). Among all infected patients, the time from diagnosis of the infection to resolution of the infection for all survivors was 7 to 98 days (mean: 26.41 days; median: 21 days). Forty-eight (90.6%) patients completely healed their wounds, and 45 (84.9%) patients are currently alive. Thirty-eight patients had a cyanotic cardiac diagnosis and 15 had an acyanotic cardiac diagnosis. The most common bacteria isolated from the blood or wound cultures was Staphylococcus aureus . Six of 53 patients died. Causes of death are as follows: three from respiratory failure, one from sepsis, one from hypoxic ischemic encephalopathy, and one from exsanguination leading to cardiac arrest Conclusions: Complicated sternal wound infections after pediatric cardiac surgery refractory to antibiotic therapy and/or debridement can be successfully treated with NPWT and/or HBO therapy.